Carbonate chemistry in high salinity waters - Loewenthal, Richard Eric (Department of Civil Engineering, 2016)
The primary objective of this investigation was to develop phase equilibrium diagrams for the carbonate system in high salinity waters, i.e. for single aqueous phase, solid-aqueous phase, gasaqueous phase and solid-aqueous-gas phases. Such diagrams have been developed for low salinity waters, viz. Deffeyes and Caldwell-Lawrence diagrams and modifications of these.